2013
DOI: 10.1002/lt.23577
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Overexpressing C-X-C Chemokine Receptor Type 4 Improve Early Liver Regeneration of Small-for-Size Liver Grafts

Abstract: Mesenchymal stem cell (MSC) therapy can prevent hepatic parenchymal cell loss and promote tissue repair. However, poor MSC engraftment is one of the primary barriers to the effectiveness of cell therapy because culture-expanded MSCs progressively downregulate C-X-C chemokine receptor type 4 (CXCR4) expression and lose their ability to migrate toward a concentration gradient of stromal cell-derived factor 1a (SDF1a). In this study, we investigated whether a CXCR4-MSC infusion could protect hepatocytes and stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…It was observed in our study that null-BMSCs expressed only small amounts of CXCR4. Transplantation of BMSCs that overexpressed CXCR4 led to significant protection against ovariectomy-induced bone loss (4), augmented myoangiogenesis in infarcted myocardium (3,16,43), and induced early liver regeneration of small-for-size liver grafts (7). These observations suggest that overexpression of CXCR4 contributes to enhanced efficacy of BMSC therapy due to the increased homing ability of BMSCs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It was observed in our study that null-BMSCs expressed only small amounts of CXCR4. Transplantation of BMSCs that overexpressed CXCR4 led to significant protection against ovariectomy-induced bone loss (4), augmented myoangiogenesis in infarcted myocardium (3,16,43), and induced early liver regeneration of small-for-size liver grafts (7). These observations suggest that overexpression of CXCR4 contributes to enhanced efficacy of BMSC therapy due to the increased homing ability of BMSCs.…”
Section: Discussionmentioning
confidence: 96%
“…Regulation of CXCR4 expression is expected to influence the directional homing of infused BMSCs. In addition, the SDF-1/CXCR4 axis is also reported to be required for the paracrine actions of BMSCs (7,23). Regulation of CXCR4 expression is also expected to contribute to the paracrine actions of BMSCs.…”
mentioning
confidence: 93%
“…Adherent cells were fixed with 4% paraformaldehyde for 15 min at room temperature, stained 10 min with 0.5% crystal violet, and counted. The number of transmembrane cells in 10 different fields under the microscope was averaged (26).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies emphasizing MSC-assisted regenerative effects were reported in the treatment of the remnant liver [91] and the small-size liver graft [92], which serves as a significant challenge in patients receiving living-related liver transplants. In animal studies, CXCR4 overexpression of MSCs prolonged MSC engraftment, and this finding was associated with significant increased hepatocyte proliferation and improvement of the survival time of liver.…”
Section: Liver Transplantationmentioning
confidence: 98%